Company Characteristics, Dominant Personalities in Board Committees and Internet Financial Disclosures by Malaysian Listed Companies (Malaysian Management Journal, 2016)
This paper investigates whether the internet financial disclosure can be explained by a company’s characteristics and the dominant personalities in board committees of the Malaysian listed companies. Ten hypotheses were tested using data collected from 194 Malaysian listed companies’ websites. Specifically, this paper examines the relationship between the internet financial disclosures (IFD) and the variables, namely internationality, leverage, foreign shareholders, level of technology, firm age, number of shareholders, listing status, dominant personalities in the audit committee, and chairmen of audit and nomination committees. It is found that the level of technology, firm age, number of shareholders and listing status significantly affect the level of IFD. However, the dominant personalities in the audit and nomination committees affect negatively the level of IFD in Malaysia. The study provides some evidence to support the signaling theory and the cost and benefit hypothesis in relation to internet disclosure.